An Orthokeratinized Odontogenic Cyst in an 8-Year-Old: A Case Report with Differential Diagnosis - Chan M. Park; Jeffrey A. Elo; Mark Mintline; Elizabeth Orbeta; Stephen Seongeun Koh (Journal of the California Dental Association)
Background Orthokeratinized odontogenic cyst (OOC) is a rare developmental odontogenic cyst that is clinically and histomorphologically different than odontogenic keratocyst (OKC).Case Description OOC is a distinct entity from OKC with a unique biological behavior, pathogenesis, and prognosis. The distinction between these entities is paramount because unlike OKCs, OOCs rarely recur after simple enucleation and are not associated with nevoid basal cell carcinoma syndrome. We present a case of an 8-year-old male with an OOC of the right posterior mandible along with a differential diagnosis and discussion of OOCs and its common mimics.